Multifunctional flame retardant polystyrene foam with synergistic coating and method of making

CN122878624APending Publication Date: 2026-10-09SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610950355.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

现有单组分或简单复合涂层难以兼顾上述多种性能,且不同功能组分之间往往存在相互制约,难以实现协同增效

Benefits of technology

[0049]1、本发明制备所得具有多元协效涂层的多功能阻燃聚苯乙烯泡沫材料,通过在聚苯乙烯泡沫材料表面先后构建界面结合层、导电功能层、阻燃功能层及疏水防护层,形成多层涂层协同功能结构。其中,界面结合层主要用于改善后续功能层与聚苯乙烯泡沫基体之间的界面结合强度,提高整体涂层稳定性和耐久性;通过聚多巴胺改性界面结合层,在基体表面形成具有丰富儿茶酚基和氨基结构的粘附层,为银离子的络合及原位还原提供活性位点,从而实现银层的均匀沉积和牢固结合;通过镀银所构建的导电功能层形成连续导电反射网络;阻燃功能层中,聚磷酸铵在燃烧过程中释放磷酸及聚磷酸促进炭层形成,氮化硼片层则构建热质传递阻隔网络,两者协同提高材料的阻燃性能和隔热性能;疏水防护层具有微纳粗糙结构,提高材料表面的疏水性能和耐候性能,同时降低表面污染,提高长期服役稳定性。各功能层之间结合紧密,形成连续稳定的多层协同结构,使材料同时具备阻燃、导电、防水、隔热及辐射热管理等功能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878624A_ABST
    Figure CN122878624A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of flame-retardant functional polystyrene foaming material, and relates to a multifunctional flame-retardant polystyrene foam material with a multi-element synergistic coating and a preparation method thereof. The present application forms a multi-layer coating synergistic functional structure by successively constructing an interface bonding layer, a conductive functional layer, a flame-retardant functional layer and a hydrophobic protective layer on the surface of the polystyrene foam material. The interface bonding layer is modified by polydopamine to endow it with excellent interface adhesion capacity. The conductive functional layer is formed by silver plating to form a continuous conductive reflection network. The flame-retardant functional layer realizes efficient flame-retardant and heat insulation synergy through BN@APP composite flame-retardant units. The hydrophobic protective layer further improves the weather resistance, waterproof performance and radiant heat management capacity of the material by constructing a PDMS / SiO2 composite coating, so as to prepare a multifunctional flame-retardant polystyrene foam material with flame-retardant performance, mechanical performance, conductive performance, hydrophobic performance and radiation refrigeration potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of flame-retardant functional polystyrene foam materials, and relates to a multifunctional flame-retardant polystyrene foam material with a multi-element synergistic coating and its preparation method. The multifunctional flame-retardant polystyrene foam material has flame-retardant properties, electrical conductivity, hydrophobic properties, thermal insulation properties and weather resistance properties, and also has the potential for antistatic properties, radiative heat management and passive cooling. Background Technology

[0002] Polystyrene (PS) foam materials mainly include molded polystyrene foam (EPS) and extruded polystyrene foam (XPS). Due to their advantages such as light weight, low thermal conductivity, excellent thermal insulation performance, and low cost, they are widely used in building exterior wall insulation, cold chain transportation, and packaging cushioning. With the continuous improvement of building energy efficiency requirements, polystyrene foam materials have become one of the most widely used organic insulation materials in building insulation systems.

[0003] However, polystyrene foam is mainly composed of carbon and hydrogen elements. It has a well-developed cellular structure, a large specific surface area, thin cell walls, and contains a large amount of flammable gas, making it highly ignitable and capable of rapid combustion. During combustion, it is accompanied by melting and dripping, releasing a large amount of heat and smoke, posing a serious fire hazard. Especially in building external insulation systems, polystyrene foam can easily cause flame spread in the event of a fire, seriously threatening lives and property. Therefore, improving the flame-retardant properties of polystyrene foam has become an important research direction in this field.

[0004] Currently, the main industrial method to improve the flame retardant properties of polystyrene foam is to add brominated flame retardants to the polystyrene foam raw materials. However, with the complete ban on hexabromocyclododecane (HBCD), methyl octabromoether and brominated SBS have become commonly used flame retardants in polystyrene foam materials. However, brominated flame retardants easily release corrosive and toxic substances such as hydrogen bromide and dioxins during combustion, posing potential hazards to the ecological environment and human health. Therefore, the development of halogen-free flame retardant technology has become an important direction for the development of polystyrene foam materials.

[0005] Replacing bromine-based flame retardants with phosphorus-based ones is a key technical route for halogen-free materials, but traditional bulk addition methods still have many problems. On the one hand, high amounts of flame retardants can easily reduce the mechanical and processing properties of the material; on the other hand, flame retardants have poor compatibility with the polystyrene matrix, easily migrating and precipitating, affecting the long-term stability of the material. Furthermore, because polystyrene molecules lack oxygen-containing groups necessary for char formation, relying solely on phosphorus-based flame retardants often fails to form a dense and stable char layer, resulting in limited flame retardant efficiency.

[0006] In recent years, surface functional coating technology has gradually become a research hotspot because it can impart flame-retardant properties to polystyrene foam without altering its main structure and processing technology. By constructing a barrier layer, ceramicized layer, or expanded char layer on the surface of polystyrene foam, the transfer of heat, oxygen, and combustible volatiles can be effectively hindered, thereby significantly improving the flame-retardant performance of the material. Compared with traditional bulk flame-retardant technology, surface coating has advantages such as requiring less flame retardant, simpler processing, and minimal impact on the foam's inherent properties.

[0007] However, most existing flame-retardant coating systems focus on a single flame-retardant function, generally suffering from insufficient adhesion between the coating and the substrate, poor mechanical stability, limited weather resistance, and limited functionality. Meanwhile, with the development of green building and high-performance insulation materials, there is a growing demand for polystyrene foam materials to achieve multiple integrated functions, including flame retardancy, heat insulation, smoke suppression, weather resistance, mechanical reinforcement, and radiant heat management. Existing single-component or simple composite coatings struggle to simultaneously achieve these multiple properties, and different functional components often exhibit mutual constraints, making synergistic effects difficult to realize.

[0008] Therefore, there is an urgent need to develop a functional coating system based on multi-component synergistic design. By constructing the synergistic effect between flame-retardant components, inorganic shielding components and functional nanofillers, this system can endow PS foam with excellent flame-retardant properties while achieving multiple functions such as heat insulation, reinforcement, weather resistance and thermal management, thereby meeting the application needs of high-safety and multifunctional polystyrene foam materials in the building insulation field. Summary of the Invention

[0009] To address the shortcomings of existing technologies, this invention provides a multifunctional flame-retardant polystyrene foam material with a multi-layer synergistic coating and its preparation method. This invention constructs an interfacial bonding layer, a conductive functional layer, a flame-retardant functional layer, and a hydrophobic protective layer sequentially on the surface of the polystyrene foam material, forming a multi-layered synergistic coating structure. Specifically, the polydopamine-modified interfacial bonding layer imparts excellent interfacial adhesion; the silver-plated conductive functional layer forms a continuous conductive reflective network; the flame-retardant functional layer achieves efficient flame retardancy and thermal insulation synergy through BN@APP composite flame-retardant units; and the hydrophobic protective layer, constructed with a PDMS / SiO2 composite coating, further improves the material's weather resistance, waterproof performance, and radiative heat management capabilities. This results in a multifunctional flame-retardant polystyrene foam material possessing flame retardant properties, mechanical properties, conductive properties, hydrophobic properties, and radiative cooling potential.

[0010] To achieve the above objectives, the present invention employs a technical solution consisting of the following technical measures.

[0011] This invention provides a method for preparing a multifunctional flame-retardant polystyrene foam material with a multi-component synergistic coating, comprising the following steps:

[0012] (1) Use uncoated polystyrene foam as the matrix;

[0013] (2) Styrene-acrylate copolymer emulsion is prepared at a concentration of 70~90 g / m 2 The amount of material used is coated onto the surface of the substrate described in step (1), and after drying, intermediate A with an interface bonding layer is obtained;

[0014] (3) The intermediate A obtained in step (2) is immersed in a polydopamine modified solution and stirred at 20~30 ℃ for 2~12 h. After drying, intermediate B with polydopamine surface modified interface bonding layer is obtained.

[0015] The polydopamine-modified solution was prepared by Tris buffer and dopamine hydrochloride, with a Tris concentration of 5-20 mmol / L, a dopamine hydrochloride concentration of 5-15 mmol / L, and a pH controlled at 8.0-9.0.

[0016] (4) The intermediate B obtained in step (3) is subjected to chemical silver plating to construct a conductive functional layer on the surface of intermediate B, thereby obtaining intermediate C;

[0017] (5) Mix hexagonal boron nitride nanosheets and ammonium polyphosphate at a mass ratio of 1: (5~10) and then prepare BN@APP composite flame retardant unit powder by dry ball milling assisted exfoliation process. Add the obtained BN@APP composite flame retardant unit powder to organosilicon modified styrene-acrylate copolymer emulsion and disperse it evenly to obtain flame retardant functional coating.

[0018] The parameters of the dry ball milling assisted stripping process include: ball milling speed of 400~800 rpm, ball milling time of 5~15 h, and ball-to-material ratio of (5~20):1;

[0019] The amount of BN@APP composite flame retardant unit powder added is 10~50 wt% of the mass of the silicone-modified styrene-acrylate copolymer emulsion.

[0020] (6) Apply the flame-retardant functional coating obtained in step (5) at a concentration of 80~130 g / m 2 The amount of product used is coated onto the surface of intermediate C obtained in step (4), and after drying and curing, a flame-retardant functional layer is formed to obtain intermediate D;

[0021] (7) Mix the polydimethylsiloxane prepolymer and the curing agent at a mass ratio of 10: (0.8~1.2) until uniform, then add hydrophobic silica particles and disperse them uniformly to obtain the PDMS / SiO2 composite coating;

[0022] The amount of hydrophobic silica particles added is 1-10 wt% of the total mass of polydimethylsiloxane prepolymer and curing agent;

[0023] (8) Apply the PDMS / SiO2 composite coating obtained in step (7) at a concentration of 70~95 g / m 2 The amount of coating used is applied to the surface of intermediate D obtained in step (6), and after curing, a hydrophobic protective layer is formed, resulting in a multifunctional flame-retardant polystyrene foam material with a multi-element synergistic coating.

[0024] In this paper, the uncoated polystyrene foam material mentioned in step (1) can be commercially available polystyrene foam material or self-made.

[0025] To better illustrate the present invention and provide a technical solution for reference, under laboratory sample conditions, the uncoated polystyrene foam material described in step (1) was prepared in-house using the following method:

[0026] The method for preparing the uncoated polystyrene foam material specifically involves pre-expanding and then foaming expandable polystyrene beads to obtain an uncoated polystyrene foam material.

[0027] The process parameters for the pre-foaming treatment include: pre-foaming pressure of 0.15~0.30 MPa, pre-foaming temperature of 96~108 ℃, heat preservation time of 1~5 min, and curing time of 4~24 h;

[0028] The process parameters for the secondary foaming molding include: foaming pressure of 0.15~0.30 MPa, foaming temperature of 115~126 ℃, and holding time of 5~10 min.

[0029] The expandable polystyrene beads are conventional chemical raw materials in the field and can be obtained commercially. Their particle size and other specifications can be selected based on the specific mechanical performance requirements of the multifunctional flame-retardant polystyrene foam material described in this invention, such as selection based on the target foaming density. It should be noted that the selection of the uncoated polystyrene foam material typically only affects the mechanical properties of the final multifunctional flame-retardant polystyrene foam material, and its selection can be based on common knowledge in the field. Therefore, although only self-made polystyrene foam material was used as the matrix in the following embodiments, this selection should not be considered a limitation on the scope of protection of this invention.

[0030] In one of the technical solutions, the drying process described in steps (2) and (3) is preferably natural drying at a temperature of 20~30 ℃, or drying at a temperature of 60 ℃ for 5~15 min.

[0031] In this article, the chemical silver plating process described in step (4) is a conventional silver plating process in the art. Those skilled in the art can directly refer to the chemical silver plating process in the existing process system for specific processing.

[0032] To better illustrate the present invention and provide a technical solution for reference, the chemical silver plating treatment in step (4) specifically includes:

[0033] A silver ammonia plating solution was prepared with the following proportions: silver nitrate concentration of 58.9 mmol / L, glucose concentration of 138.8 mmol / L, potassium sodium tartrate concentration of 8.9 mmol / L, ethanol volume fraction of 5%, and the remainder being deionized water.

[0034] The intermediate B obtained in step (3) was immersed in a silver ammonia plating solution and reacted at a temperature of 20~30 ℃ for 60 min to build a conductive functional layer on the surface of intermediate B. Then it was washed and dried in sequence to obtain intermediate C.

[0035] In one of the technical solutions, the uniform dispersion in step (5) is preferably achieved by first magnetically stirring at 500 rpm for 15 min, and then ultrasonically dispersing at 200 W for 20 min.

[0036] In one of the technical solutions, the drying and curing treatment in step (6) is preferably carried out at a temperature of 20~30 ℃ for at least 24 h.

[0037] In this article, the curing agent mentioned in step (7) is a conventional curing agent selection for crosslinking polymerization of polydimethylsiloxane prepolymer. Alternatively, the polydimethylsiloxane prepolymer and curing agent can be specifically selected by directly using commercially available two-component addition-type polydimethylsiloxane, such as Dow Corning Sylgard 184.

[0038] In this paper, the hydrophobic silica particles mentioned in step (7) are silica particles with hydrophobic surface modification treatment, which can be obtained directly from commercial products or made by conventional chemical modification methods.

[0039] In one of the technical solutions, the average particle size of the hydrophobic silica particles in step (7) is preferably 10~100 nm.

[0040] In one of the technical solutions, the uniform dispersion in step (7) is preferably achieved by mechanical stirring at a speed of 900 rpm for 15 min.

[0041] In one of the technical solutions, the curing treatment in step (8) is preferably performed at a temperature of 60 °C for 4 h.

[0042] Generally, the coating methods described in this article can refer to conventional coating methods, such as spraying, brushing, or scraping.

[0043] In this document, the mixing, maturation, washing, drying, and stirring processes all follow conventional principles in chemical processes, and those skilled in the art can perform the specific operations based on common knowledge.

[0044] One of the inventive points of this invention is that, addressing the problems of existing polystyrene foam materials such as flammability, limited functionality, poor weather resistance, and insufficient adhesion and easy detachment of traditional flame-retardant coatings to the substrate, this invention constructs a multi-layered synergistic functional structure on the surface of polystyrene foam by sequentially building an interface bonding layer, a conductive functional layer, a flame-retardant functional layer, and a hydrophobic protective layer. Through the synergistic effect of styrene-acrylate copolymer emulsion and polydopamine, a stable interface bonding layer is constructed on the surface of the polystyrene foam, significantly improving the bonding strength between the subsequent functional layers and the substrate. Utilizing the complexation and reduction effects of abundant catechol and amino groups on the polydopamine surface on silver ions, uniform deposition of the conductive functional layer is achieved, constructing a continuous conductive network and a high-reflectivity interface, endowing the material with conductive, antistatic, and solar reflective functions.

[0045] Furthermore, this invention employs a dry ball milling-assisted exfoliation process to prepare BN@APP composite flame-retardant unit powder. It utilizes the thermal expansion and char formation promoted by ammonium polyphosphate (APP) under heating conditions, along with the heat and mass transfer barrier effect of boron nitride (BN) two-dimensional sheets, to construct a synergistic flame-retardant mechanism of "char formation-barrier." During combustion, APP decomposes to release polyphosphate, promoting the formation of a continuous and dense char layer. The BN sheets form a labyrinthine barrier structure within the char layer, effectively inhibiting the transfer of heat, oxygen, and combustible volatiles, improving char layer stability and flame-retardant efficiency, and achieving a synergistic enhancement of condensed-phase flame retardancy and physical shielding flame retardancy. Simultaneously, the high thermal conductivity of BN promotes localized heat diffusion, reduces heat concentration effects, and improves the material's thermal stability and structural integrity.

[0046] Furthermore, this invention constructs a PDMS / SiO2 composite coating in the outermost hydrophobic protective layer, forming a low surface energy interface with a micro-nano rough structure. This not only endows the material with excellent hydrophobic, antifouling, and weather-resistant properties but also reduces the corrosive effect of environmental moisture on the flame-retardant and conductive layers, improving the long-term service stability of the multifunctional coating system. Simultaneously, the high solar reflectivity of the conductive functional layer synergistically complements the radiative characteristics of the PDMS / SiO2 composite in the mid-infrared band, enabling the material to possess both radiative heat management and passive cooling potential, providing a new technological approach for building energy conservation and green low-carbon applications.

[0047] This invention achieves complementary advantages and synergistic effects among different functional components by constructing a multi-layered synergistic structure of "interface enhancement, conductive reflection, flame retardancy and thermal insulation, and hydrophobic protection." Without altering the main structure and foaming process of polystyrene foam, it simultaneously endows the material with excellent flame retardant, conductive, hydrophobic, thermal insulation, and weather resistance properties. This overcomes the problems of large amounts of flame retardant added, decreased mechanical properties, deteriorated processing performance, and limited functionality in traditional bulk flame retardant technologies, providing a new technical route for the high-performance and multi-functional development of polystyrene foam materials.

[0048] The present invention has the following beneficial effects:

[0049] 1. The multifunctional flame-retardant polystyrene foam material with a multi-element synergistic coating prepared by this invention forms a multi-layer coating synergistic functional structure by sequentially constructing an interface bonding layer, a conductive functional layer, a flame-retardant functional layer, and a hydrophobic protective layer on the surface of the polystyrene foam material. The interface bonding layer mainly improves the interfacial bonding strength between the subsequent functional layers and the polystyrene foam matrix, enhancing the overall coating stability and durability. The polydopamine-modified interface bonding layer forms an adhesion layer with abundant catechol and amino groups on the matrix surface, providing active sites for the complexation and in-situ reduction of silver ions, thereby achieving uniform deposition and firm bonding of the silver layer. The conductive functional layer constructed through silver plating forms a continuous conductive reflective network. In the flame-retardant functional layer, ammonium polyphosphate releases phosphoric acid and polyphosphoric acid during combustion, promoting char layer formation, while the boron nitride sheet layer constructs a heat and mass transfer barrier network; both synergistically improve the flame-retardant and heat-insulating properties of the material. The hydrophobic protective layer has a micro-nano rough structure, improving the hydrophobicity and weather resistance of the material surface, while reducing surface contamination and improving long-term service stability. The functional layers are tightly integrated to form a continuous and stable multi-layered synergistic structure, enabling the material to simultaneously possess functions such as flame retardancy, electrical conductivity, waterproofing, heat insulation, and radiant heat management.

[0050] 2. This invention establishes the synergistic relationship between key technologies such as polydopamine interface activation, in-situ silver deposition, BN@APP synergistic flame retardancy, and PDMS surface functionalization, revealing the structure-property relationship between the multilayer functional coating structure and the comprehensive material properties, providing a theoretical basis for the surface functionalization design of polymer foam materials. This invention not only effectively improves the fire safety performance of polystyrene foam materials but also addresses the needs of building energy conservation, durability protection, and functional integration. It is conducive to promoting the development of halogen-free flame-retardant insulation materials and upgrading traditional polystyrene insulation materials towards high safety, multifunctionality, and green low-carbon development, resulting in significant social, economic, and ecological benefits. Attached Figure Description

[0051] Figure 1These are scanning electron microscope (SEM) images of the coating surfaces and cross-sections of intermediates C and D obtained in Example 1 of this invention, as well as the final multifunctional flame-retardant polystyrene foam material sample. Specifically, silver-plated EPS corresponds to intermediate C, flame-retardant coated EPS corresponds to intermediate D, and MF-EPS corresponds to the final multifunctional flame-retardant polystyrene foam material sample.

[0052] Figure 2 These are elemental analysis (EDS) images of the coating surface and cross-section of intermediate C obtained in Example 1 of this invention and the finally prepared multifunctional flame-retardant polystyrene foam material sample. The silver-plated EPS corresponds to intermediate C, and MF-EPS corresponds to the finally prepared multifunctional flame-retardant polystyrene foam material sample.

[0053] Figure 3 The images show photographs of the substrate, intermediate B, and intermediate C obtained in Example 1 of this invention, as well as photographs of the conductivity testing process. EPS foam corresponds to the substrate, EPS foam (PDA modified) corresponds to intermediate B, and EPS foam (silver-plated surface) corresponds to intermediate C. Intermediate C was used as the test sample for the conductivity test.

[0054] Figure 4 This is a bar chart comparing the electromagnetic shielding performance of the matrix and the finally prepared multifunctional flame-retardant polystyrene foam material sample obtained in Example 1 of this invention. EPS corresponds to the matrix, MF-EPS corresponds to the finally prepared multifunctional flame-retardant polystyrene foam material sample; SER represents the reflection shielding effectiveness, SEA represents the absorption shielding effectiveness, and SET represents the total electromagnetic shielding effectiveness.

[0055] Figure 5 These are photographs showing the water contact angle of the matrix, intermediate D, and the final multifunctional flame-retardant polystyrene foam material sample obtained in Example 1 of this invention. EPS corresponds to the matrix, EPS (flame-retardant coating) corresponds to intermediate D, and MF-EPS corresponds to the final multifunctional flame-retardant polystyrene foam material sample.

[0056] Figure 6 These are photographs of intermediate D obtained in Example 1 of this invention and the final multifunctional flame-retardant polystyrene foam material sample, along with photos of the combustion performance testing process. EPS foam (flame-retardant coating) corresponds to intermediate D, and MF-EPS (PDMS coating) corresponds to the final multifunctional flame-retardant polystyrene foam material sample. The multifunctional flame-retardant polystyrene foam material sample was used as the test sample for the combustion performance test. Detailed Implementation

[0057] To further understand the present invention, preferred embodiments are described below with reference to examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims. Those skilled in the art can refer to the content of this document to appropriately improve the process parameters. In particular, it should be noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included within the scope of the present invention. The methods and applications of the present invention have been described through preferred embodiments, and those skilled in the art can obviously make modifications or appropriate changes and combinations to the methods and applications described herein without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention. Although it is believed that those skilled in the art will fully understand the following terms, the following definitions are set forth to help illustrate the subject matter disclosed in the present invention.

[0058] This invention provides a method for preparing a multifunctional flame-retardant polystyrene foam material with a multi-component synergistic coating, comprising the following steps:

[0059] (1) Use uncoated polystyrene foam as the matrix;

[0060] (2) Styrene-acrylate copolymer emulsion is prepared at a concentration of 70~90 g / m 2 The amount of material used is coated onto the surface of the substrate described in step (1), and after drying, intermediate A with an interface bonding layer is obtained;

[0061] (3) The intermediate A obtained in step (2) is immersed in a polydopamine modified solution and stirred at 20~30 ℃ for 2~12 h. After drying, intermediate B with polydopamine surface modified interface bonding layer is obtained.

[0062] The polydopamine-modified solution was prepared by Tris buffer and dopamine hydrochloride, with a Tris concentration of 5-20 mmol / L, a dopamine hydrochloride concentration of 5-15 mmol / L, and a pH controlled at 8.0-9.0.

[0063] (4) The intermediate B obtained in step (3) is subjected to chemical silver plating to construct a conductive functional layer on the surface of intermediate B, thereby obtaining intermediate C;

[0064] (5) Mix hexagonal boron nitride nanosheets and ammonium polyphosphate at a mass ratio of 1: (5~10) and then prepare BN@APP composite flame retardant unit powder by dry ball milling assisted exfoliation process. Add the obtained BN@APP composite flame retardant unit powder to organosilicon modified styrene-acrylate copolymer emulsion and disperse it evenly to obtain flame retardant functional coating.

[0065] The parameters of the dry ball milling assisted stripping process include: ball milling speed of 400~800 rpm, ball milling time of 5~15 h, and ball-to-material ratio of (5~20):1;

[0066] The amount of BN@APP composite flame retardant unit powder added is 10~50 wt% of the mass of the silicone-modified styrene-acrylate copolymer emulsion.

[0067] (6) Apply the flame-retardant functional coating obtained in step (5) at a concentration of 80~130 g / m 2 The amount of product used is coated onto the surface of intermediate C obtained in step (4), and after drying and curing, a flame-retardant functional layer is formed to obtain intermediate D;

[0068] (7) Mix the polydimethylsiloxane prepolymer and the curing agent at a mass ratio of 10: (0.8~1.2) until uniform, then add hydrophobic silica particles and disperse them uniformly to obtain the PDMS / SiO2 composite coating;

[0069] The amount of hydrophobic silica particles added is 1-10 wt% of the total mass of polydimethylsiloxane prepolymer and curing agent;

[0070] (8) Apply the PDMS / SiO2 composite coating obtained in step (7) at a concentration of 70~95 g / m 2 The amount of coating used is applied to the surface of intermediate D obtained in step (6), and after curing, a hydrophobic protective layer is formed, resulting in a multifunctional flame-retardant polystyrene foam material with a multi-element synergistic coating.

[0071] In this paper, the uncoated polystyrene foam material mentioned in step (1) can be commercially available polystyrene foam material or self-made.

[0072] To better illustrate the present invention and provide an embodiment for reference, under laboratory sample conditions, the uncoated polystyrene foam material described in step (1) was prepared in-house using the following method:

[0073] The method for preparing the uncoated polystyrene foam material specifically involves pre-expanding and then foaming expandable polystyrene beads to obtain an uncoated polystyrene foam material.

[0074] The process parameters for the pre-foaming treatment include: pre-foaming pressure of 0.15~0.30 MPa, pre-foaming temperature of 96~108 ℃, heat preservation time of 1~5 min, and curing time of 4~24 h;

[0075] The process parameters for the secondary foaming molding include: foaming pressure of 0.15~0.30 MPa, foaming temperature of 115~126 ℃, and holding time of 5~10 min.

[0076] The expandable polystyrene beads are conventional chemical raw materials in the field and can be obtained commercially. Their particle size and other specifications can be selected based on the specific mechanical performance requirements of the multifunctional flame-retardant polystyrene foam material described in this invention, such as selection based on the target foaming density. It should be noted that the selection of the uncoated polystyrene foam material typically only affects the mechanical properties of the final multifunctional flame-retardant polystyrene foam material, and its selection can be based on common knowledge in the field. Therefore, although only self-made polystyrene foam material was used as the matrix in the following embodiments, this selection should not be considered a limitation on the scope of protection of this invention.

[0077] In one embodiment, the drying process in steps (2) and (3) is preferably natural drying at a temperature of 20-30°C, or drying at a temperature of 60°C for 5-15 minutes.

[0078] In one embodiment, the amount of styrene-acrylate copolymer emulsion used in step (2) is 70~90 g / m³. 2 For example, 70 g / m 2 75 g / m 2 80 g / m 2 85 g / m 2 90 g / m 2 Or any range or point value between them.

[0079] In one embodiment, the Tris concentration in step (3) is 5 to 20 mmol / L, for example, 5 mmol / L, 6 mmol / L, 7 mmol / L, 8 mmol / L, 9 mmol / L, 10 mmol / L, 11 mmol / L, 12 mmol / L, 13 mmol / L, 14 mmol / L, 15 mmol / L, 16 mmol / L, 17 mmol / L, 18 mmol / L, 19 mmol / L, 20 mmol / L or any range or point value between them; the dopamine hydrochloride concentration is 5 to 15 mmol / L, for example, 5 mmol / L, 6 mmol / L, 7 mmol / L, 8 mmol / L, 9 mmol / L, 10 mmol / L, 11 mmol / L, 12 mmol / L, 13 mmol / L, 14 mmol / L, 15 mmol / L or any range or point value between them.

[0080] In this article, the chemical silver plating process described in step (4) is a conventional silver plating process in the art. Those skilled in the art can directly refer to the chemical silver plating process in the existing process system for specific processing.

[0081] To better illustrate the present invention and provide a reference embodiment, the chemical silver plating treatment in step (4) specifically includes:

[0082] A silver ammonia plating solution was prepared with the following proportions: silver nitrate concentration of 58.9 mmol / L, glucose concentration of 138.8 mmol / L, potassium sodium tartrate concentration of 8.9 mmol / L, ethanol volume fraction of 5%, and the remainder being deionized water.

[0083] The intermediate B obtained in step (3) was immersed in a silver ammonia plating solution and reacted at a temperature of 20~30 ℃ for 60 min to build a conductive functional layer on the surface of intermediate B. Then it was washed and dried in sequence to obtain intermediate C.

[0084] In one embodiment, the uniform dispersion in step (5) is preferably achieved by first magnetically stirring at 500 rpm for 15 min, and then ultrasonically dispersing at 200 W for 20 min.

[0085] In one embodiment, the hexagonal boron nitride nanosheets in step (5) are mixed with ammonium polyphosphate at a mass ratio of 1:(5~10), for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any range or point value between them; the amount of BN@APP composite flame retardant unit powder added is 10~50 wt% of the mass of the silicone-modified styrene-acrylate copolymer emulsion, for example, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, 30 wt%, 31 wt%, 32 wt%, 33 wt%, 34 wt%, 35 wt%, 36 wt%, 37 wt%, 38 wt%. wt%, 39 wt%, 40 wt%, 41 wt%, 42 wt%, 43 wt%, 44 wt%, 45 wt%, 46 wt%, 47 wt%, 48 wt%, 49 wt%, 50 wt%, or any range or point value between them.

[0086] In one embodiment, the drying and curing treatment in step (6) is preferably carried out at a temperature of 20~30 °C for at least 24 h.

[0087] In one embodiment, the amount of flame-retardant functional coating used in step (6) is 80~130 g / m³. 2 For example, 80 g / m 2 85 g / m 2 90 g / m 2 95 g / m 2 100 g / m 2 105 g / m 2 110 g / m 2 115 g / m 2 120 g / m 2 125 g / m 2 130 g / m 2 Or any range or point value between them.

[0088] In this article, the curing agent mentioned in step (7) is a conventional curing agent selection for crosslinking polymerization of polydimethylsiloxane prepolymer. Alternatively, the polydimethylsiloxane prepolymer and curing agent can be specifically selected by directly using commercially available two-component addition-type polydimethylsiloxane, such as Dow Corning Sylgard 184.

[0089] In this paper, the hydrophobic silica particles mentioned in step (7) are silica particles with hydrophobic surface modification treatment, which can be obtained directly from commercial products or made by conventional chemical modification methods.

[0090] In one embodiment, the average particle size of the hydrophobic silica particles in step (7) is preferably 10 to 100 nm.

[0091] In one embodiment, the uniform dispersion in step (7) is preferably achieved by mechanical stirring at a speed of 900 rpm for 15 min.

[0092] In one embodiment, the amount of hydrophobic silica particles added in step (7) is 1 to 10 wt% of the total mass of polydimethylsiloxane prepolymer and curing agent, for example, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt% or any range or point value between them.

[0093] In one embodiment, the curing treatment in step (8) is preferably performed at a temperature of 60 °C for 4 h.

[0094] In one embodiment, the amount of PDMS / SiO2 composite coating used in step (8) is 70~95 g / m 2 For example, 70 g / m 2 75 g / m 2 80 g / m 2 85 g / m 2 90 g / m 2 95 g / m 2 Or any range or point value between them.

[0095] Generally, the coating methods described in this article can refer to conventional coating methods, such as spraying, brushing, or scraping.

[0096] In this document, the mixing, maturation, washing, drying, and stirring processes all follow conventional principles in chemical processes, and those skilled in the art can perform the specific operations based on common knowledge.

[0097] One of the inventive points of this invention is that, addressing the problems of existing polystyrene foam materials such as flammability, limited functionality, poor weather resistance, and insufficient adhesion and easy detachment of traditional flame-retardant coatings to the substrate, this invention constructs a multi-layered synergistic functional structure on the surface of polystyrene foam by sequentially building an interface bonding layer, a conductive functional layer, a flame-retardant functional layer, and a hydrophobic protective layer. Through the synergistic effect of styrene-acrylate copolymer emulsion and polydopamine, a stable interface bonding layer is constructed on the surface of the polystyrene foam, significantly improving the bonding strength between the subsequent functional layers and the substrate. Utilizing the complexation and reduction effects of abundant catechol and amino groups on the polydopamine surface on silver ions, uniform deposition of the conductive functional layer is achieved, constructing a continuous conductive network and a high-reflectivity interface, endowing the material with conductive, antistatic, and solar reflective functions.

[0098] Furthermore, this invention employs a dry ball milling-assisted exfoliation process to prepare BN@APP composite flame-retardant unit powder. It utilizes the thermal expansion and char formation promoted by ammonium polyphosphate (APP) under heating conditions, along with the heat and mass transfer barrier effect of boron nitride (BN) two-dimensional sheets, to construct a synergistic flame-retardant mechanism of "char formation-barrier." During combustion, APP decomposes to release polyphosphate, promoting the formation of a continuous and dense char layer. The BN sheets form a labyrinthine barrier structure within the char layer, effectively inhibiting the transfer of heat, oxygen, and combustible volatiles, improving char layer stability and flame-retardant efficiency, and achieving a synergistic enhancement of condensed-phase flame retardancy and physical shielding flame retardancy. Simultaneously, the high thermal conductivity of BN promotes localized heat diffusion, reduces heat concentration effects, and improves the material's thermal stability and structural integrity.

[0099] Furthermore, this invention constructs a PDMS / SiO2 composite coating in the outermost hydrophobic protective layer, forming a low surface energy interface with a micro-nano rough structure. This not only endows the material with excellent hydrophobic, antifouling, and weather-resistant properties but also reduces the corrosive effect of environmental moisture on the flame-retardant and conductive layers, improving the long-term service stability of the multifunctional coating system. Simultaneously, the high solar reflectivity of the conductive functional layer synergistically complements the radiative characteristics of the PDMS / SiO2 composite in the mid-infrared band, enabling the material to possess both radiative heat management and passive cooling potential, providing a new technological approach for building energy conservation and green low-carbon applications.

[0100] This invention achieves complementary advantages and synergistic effects among different functional components by constructing a multi-layered synergistic structure of "interface enhancement, conductive reflection, flame retardancy and thermal insulation, and hydrophobic protection." Without altering the main structure and foaming process of polystyrene foam, it simultaneously endows the material with excellent flame retardant, conductive, hydrophobic, thermal insulation, and weather resistance properties. This overcomes the problems of large amounts of flame retardant added, decreased mechanical properties, deteriorated processing performance, and limited functionality in traditional bulk flame retardant technologies, providing a new technical route for the high-performance and multi-functional development of polystyrene foam materials.

[0101] The present application will be further explained in detail below with reference to embodiments. However, those skilled in the art should understand that these embodiments are provided for illustrative purposes only and are not intended to limit the present application.

[0102] Example

[0103] The embodiments of this application will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be construed as limiting the scope of this application. Where specific conditions are not specified in the examples, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all commercially available conventional products. This application should not be construed as being limited to the specific embodiments described.

[0104] 1. Raw materials

[0105] Expandable polystyrene beads (EPS), H-SB, industrial grade, Ningbo Xinqiao Chemical Co., Ltd.

[0106] Styrene-acrylate copolymer emulsion (styrene-acrylic emulsion), Yuso Chemical Technology;

[0107] Organosilicon-modified styrene-acrylate copolymer emulsion (silicone-acrylic emulsion), Yuso Chemical Technology;

[0108] Dopamine hydrochloride (DA), ≥98%, reagent grade, Aladdin;

[0109] Tris(hydroxymethyl)aminomethane (Tris), ≥99%, reagent grade, Aladdin;

[0110] Silver nitrate, Tianjin Yongda Chemical Reagent Co., Ltd.

[0111] Anhydrous glucose, ≥99.5%, reagent grade, Aladdin;

[0112] Potassium sodium tartrate, ≥99%, reagent grade, Maclean's;

[0113] Hexagonal boron nitride (BN) nanosheets, average sheet diameter 1 µm, ≥98.5%, reagent grade, Maclean;

[0114] Ammonium polyphosphate (APP), n≥1000, reagent grade, source leaf;

[0115] The polydimethylsiloxane prepolymer and curing agent are a two-component addition-type polydimethylsiloxane (Dow Corning Sylgard 184).

[0116] Hydrophobic silica particles with an average particle size of 20 nm are an outstanding new nanomaterial.

[0117] 2. Testing Methods

[0118] (1) Scanning electron microscopy (SEM) test

[0119] The surface and cross-sectional morphology of the coating were observed using a scanning electron microscope (JSM-5900LV, NEC Corporation, Japan). The samples were sputter-coated with gold prior to testing to improve surface conductivity.

[0120] (2) Elemental Analysis (EDS) Test

[0121] The elemental distribution of the coating cross section and surface was analyzed using an Octane Elect Super energy dispersive spectrometer (EDAX, USA) mounted on a scanning electron microscope.

[0122] (3) Combustion performance test

[0123] A direct flame burning test was conducted on the samples using an alcohol lamp to preliminarily evaluate their flame retardant properties. During the test, the samples were fixed to a fixture, with one end or surface exposed to the alcohol lamp flame, and the ignition time was set to 10 seconds. After removing the ignition source, the afterflame time, whether melting and dripping occurred, whether self-extinguishing occurred after the flame was removed, and the formation of the char layer after combustion were recorded. Further vertical burning tests were conducted according to UL-94 standards using a JT-HVR5455 instrument. The sample dimensions were 125 × 13 × 12 mm. 3 .

[0124] (4) Cone calorimeter (CCT) test

[0125] The combustion behavior of the samples was evaluated using a cone calorimeter (model 6810, Yangyi Wolchi, China). The sample dimensions were 100 × 100 × 20 mm. 3 Horizontally placed and exposed to 35 kW·m -2 Under the external heat flux density.

[0126] (5) Raman spectroscopy analysis

[0127] Raman spectroscopy analysis of the carbon residue was performed using an inVia Reflex Raman imaging microscope (Renishaw, UK) to study its graphitization degree and carbon structure.

[0128] (6) X-ray photoelectron spectroscopy (XPS) analysis

[0129] The surface elemental composition and chemical state of different coated foam residues were analyzed using an X-ray photoelectron spectroscopy (XSAM800, Kratos, UK) instrument.

[0130] (7) Mechanical property testing

[0131] The compression and bending properties of the samples were measured using a universal testing machine (INSTRON 5966, USA). The compression test sample dimensions were 25 × 25 × 13 mm. 3 The testing speed was 2 mm / min. The bending test sample was cut to a size of 100 × 25 × 13 mm. 3 The test rate was also 2 mm / min.

[0132] (8) Conductivity test

[0133] The surface resistance of the sample was tested using a digital multimeter (Victor VC890D) to evaluate its conductivity. During the test, the multimeter was set to resistance test mode, and the two test probes were brought into contact with the silver plating layer on the sample surface.

[0134] (9) Electromagnetic shielding (EMI) test

[0135] Electromagnetic shielding performance was tested using a vector network analyzer (Keysight N5247A). Before testing, the sample was cut to a size matching the test fixture (12mm diameter circular piece), with a sample thickness controlled to 1mm, ensuring a flat surface and intact edges. The instrument was calibrated before testing to eliminate the influence of cables, fixtures, and connection ports on the test results. The sample was then placed in the test fixture, and its scattering parameters, including the reflection parameter S, were measured within a set frequency range. 11 and transmission parameter S 21The reflectance, transmittance, absorption coefficient, and electromagnetic shielding effectiveness of the sample are calculated based on the obtained S-parameters.

[0136] (10) Water contact angle (WCA) test

[0137] The water contact angle was measured using a contact angle measuring instrument (DSA30, KRÜSS, Germany). Before testing, the sample surface was cleaned and kept dry. During the test, a certain volume of deionized water was added to the sample surface using a micro-syringe. After the droplet morphology stabilized, an image was acquired, and the static water contact angle was calculated using the instrument's software. Each sample was tested at different locations at least three times, and the average value was taken as the final result.

[0138] Example 1

[0139] The preparation method of a multifunctional flame-retardant polystyrene foam material with a multi-component synergistic coating in Example 1 includes the following steps:

[0140] (1) Expandable polystyrene beads were pre-foamed and then foamed in a second process to prepare a polystyrene foam material with no coating on the surface as the matrix;

[0141] The process parameters for the pre-foaming treatment include: pre-foaming pressure of 0.2 MPa, pre-foaming temperature of 108 ℃, heat preservation time of 3 min, and curing at 20~30 ℃ for 24 h after the pre-foaming treatment.

[0142] The process parameters for the secondary foaming molding include: foaming pressure of 0.20 MPa, foaming temperature of 126 ℃, heat preservation time of 10 min, and demolding after natural cooling.

[0143] (2) Coat the substrate surface described in step (1) with the styrene-acrylate copolymer emulsion, controlling the amount used to be approximately 70 g / m³. 2 After drying in a 60 ℃ forced-air oven for 10 min, intermediate A with an interfacial bonding layer was obtained;

[0144] (3) The intermediate A obtained in step (2) is immersed in a polydopamine modified solution, stirred and reacted at 20~30 ℃ for 8 h, and then dried naturally at 20~30 ℃ to obtain intermediate B of polydopamine surface modified interface bonding layer;

[0145] The polydopamine-modified solution was prepared by Tris buffer and dopamine hydrochloride, with a Tris concentration of 10 mmol / L, a dopamine hydrochloride concentration of 8.3 mmol / L, and a pH adjusted to 8.5.

[0146] (4) The intermediate B obtained in step (3) is subjected to chemical silver plating to construct a conductive functional layer on the surface of intermediate B, thereby obtaining intermediate C;

[0147] The chemical silver plating process specifically includes:

[0148] A silver ammonia plating solution was prepared with the following proportions: silver nitrate concentration of 58.9 mmol / L, glucose concentration of 138.8 mmol / L, potassium sodium tartrate concentration of 8.9 mmol / L, ethanol volume fraction of 5%, and the remainder being deionized water.

[0149] The intermediate B obtained in step (3) was immersed in silver ammonia silver plating solution and reacted at a temperature of 20~30 ℃ for 60 min to build a conductive functional layer on the surface of intermediate B. Then it was washed with deionized water and dried naturally to obtain intermediate C.

[0150] (5) Mix 2.0 g of hexagonal boron nitride nanosheets with 15.0 g of ammonium polyphosphate evenly, and then prepare BN@APP composite flame retardant unit powder by dry ball milling assisted exfoliation process. Add 30 g of the obtained BN@APP composite flame retardant unit powder to 70 g of organosilicon modified styrene-acrylate copolymer emulsion, first stir magnetically at 500 rpm for 15 min, and then ultrasonically disperse at 200W for 20 min to obtain flame retardant functional coating.

[0151] The parameters of the dry ball milling assisted exfoliation process include: a ball milling speed of 600 rpm, a ball milling time of 10 h, a ball-to-material ratio of 10:1, and a ball milling medium of zirconia balls with diameters of 3 mm and 5 mm and a mass ratio of 1:1.

[0152] (6) Apply the flame-retardant functional coating obtained in step (5) to the surface of intermediate C obtained in step (4), controlling the amount used to be approximately 80 g / m². 2 The mixture is dried and cured at 20~30 ℃ for 24 h to form a flame-retardant functional layer, thus obtaining intermediate D.

[0153] (7) Mix 10 g of polydimethylsiloxane prepolymer with 1 g of curing agent evenly, then add 0.3 g of hydrophobic silica particles and mechanically stir at 900 rpm for 15 min to obtain PDMS / SiO2 composite coating.

[0154] (8) Apply the PDMS / SiO2 composite coating obtained in step (7) to the surface of intermediate D obtained in step (6), controlling the amount used to be approximately 70 g / m. 2The material is cured at 60 ℃ for 4 h to form a hydrophobic protective layer, resulting in a multifunctional flame-retardant polystyrene foam material with a multi-component synergistic coating.

[0155] The matrix, intermediates A-D obtained in Example 1, and the finally prepared multifunctional flame-retardant polystyrene foam material with a multi-component synergistic coating were used as samples and tested according to "2. Test Methods" above. The results are as follows. Figures 1-6 As shown.

[0156] like Figure 1 As shown, scanning electron microscopy (SEM) images demonstrate the successful construction of a hierarchical multifunctional coating on the surface of polystyrene foam (EPS). First, a dense and continuous silver layer was formed on the surface of polydopamine (PDA)-modified intermediate B, indicating the effectiveness of the PDA-assisted electroless plating process. Subsequently, a flame-retardant functional coating containing BN@APP composite flame-retardant unit powder uniformly covered the conductive functional layer, exhibiting excellent interfacial adhesion without significant cracking or delamination. After the deposition of the outermost polydimethylsiloxane (PDMS) / silica (SiO2) layer, the surface roughness significantly increased, and numerous micro / nano-scale protrusions appeared, attributed to the aggregation of hydrophobic silica nanoparticles in the PDMS matrix. This hierarchical structure not only ensures strong interfacial bonding between adjacent layers but also provides a structural basis for the synergistic realization of electromagnetic shielding, flame retardancy, hydrophobicity, and radiative cooling properties.

[0157] like Figure 2 As shown, EDS elemental analysis further confirmed the successful construction of the multi-layered coating. For the intermediate C sample, Ag was uniformly distributed on the outer surface, forming a continuous layer, indicating the effectiveness of the PDA-assisted chemical deposition process. In the MF-EPS sample, a distinct Ag-rich region was observed within the coating, while the O-containing component was distributed throughout the entire outer coating area, indicating that the conductive silver layer was successfully encapsulated by the subsequent flame-retardant and hydrophobic protective layers. This spatially separated structure facilitates the simultaneous achievement of electromagnetic shielding, flame retardancy, and surface protection functions without mutual interference.

[0158] like Figure 3 As shown, after PDA modification, the sample color changed from white to dark brown, indicating the formation of a modified polydopamine surface interface layer. Subsequently, after electroless silver plating, the sample exhibited a uniform metallic luster, indicating the formation of a continuous silver layer. Further electrical measurements showed that the surface resistance of intermediate C was below the lower limit of the multimeter, confirming the establishment of an effective conductive network. PDA modification not only promoted Ag nucleation and growth but also significantly enhanced the interfacial adhesion between the metal layer and the polymer substrate.

[0159] like Figure 4As shown, the test results indicate that the prepared multifunctional flame-retardant polystyrene foam material possesses excellent electromagnetic shielding performance, with a total electromagnetic shielding effectiveness (SET) of 37.62 dB, which is approximately 8.9 times higher than that of uncoated polystyrene foam material. Specifically, the reflective shielding effectiveness (SER) and the absorbable shielding effectiveness (SEA) reach 6.97 dB and 30.65 dB, respectively, demonstrating that the sample prepared in Example 1 of this invention can synergistically achieve electromagnetic wave reflection, absorption, and dissipation, exhibiting excellent electromagnetic protection capabilities while also possessing multiple functions such as flame retardancy, hydrophobicity, and thermal management.

[0160] like Figure 5 As shown, the constructed hydrophobic protective layer can significantly improve the surface hydrophobicity of polystyrene foam materials, reduce the residence time and adhesion of water on the material surface, thereby effectively inhibiting water penetration, freezing and contaminant adhesion, and improving the service stability and service life of the material under high humidity, low temperature and complex environmental conditions.

[0161] like Figure 6 As shown, the sample of Example 1 was subjected to a combustion test using an alcohol lamp flame. After approximately 10 seconds of flame exposure, a charred protective layer formed on the sample surface. This layer self-extinguished rapidly after the external ignition source was removed, without any continued combustion, and could not be re-ignited. Even after being covered with a hydrophobic protective layer, the sample still exhibited good flame-retardant properties, indicating good structural and functional compatibility between the hydrophobic protective layer and the flame-retardant functional layer. The BN@APP composite flame-retardant unit powder promotes the formation of an expanded char layer and an inorganic barrier layer during heating. The PDMS and hydrophobic silica components form a silicon-containing protective structure at high temperatures. These two components synergistically improve the density, integrity, and thermal insulation performance of the char layer, thereby effectively inhibiting heat transfer, oxygen diffusion, and the release of combustible gases.

[0162] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing a multifunctional flame-retardant polystyrene foam material with a multi-component synergistic coating, characterized in that... Includes the following steps: (1) Use uncoated polystyrene foam as the matrix; (2) Styrene-acrylate copolymer emulsion is prepared at a concentration of 70~90 g / m 2 The amount of material used is coated onto the surface of the substrate described in step (1), and after drying, intermediate A with an interface bonding layer is obtained; (3) The intermediate A obtained in step (2) is immersed in a polydopamine modified solution and stirred at 20~30 ℃ for 2~12 h. After drying, intermediate B with polydopamine surface modified interface bonding layer is obtained. The polydopamine-modified solution was prepared by Tris buffer and dopamine hydrochloride, with a Tris concentration of 5-20 mmol / L, a dopamine hydrochloride concentration of 5-15 mmol / L, and a pH controlled at 8.0-9.

0. (4) The intermediate B obtained in step (3) is subjected to chemical silver plating to construct a conductive functional layer on the surface of intermediate B, thereby obtaining intermediate C; (5) Mix hexagonal boron nitride nanosheets and ammonium polyphosphate at a mass ratio of 1: (5~10) and then prepare BN@APP composite flame retardant unit powder by dry ball milling assisted exfoliation process. Add the obtained BN@APP composite flame retardant unit powder to organosilicon modified styrene-acrylate copolymer emulsion and disperse it evenly to obtain flame retardant functional coating. The parameters of the dry ball milling assisted stripping process include: ball milling speed of 400~800 rpm, ball milling time of 5~15h, and ball-to-material ratio of (5~20):1; The amount of BN@APP composite flame retardant unit powder added is 10~50 wt% of the mass of the silicone-modified styrene-acrylate copolymer emulsion. (6) Apply the flame-retardant functional coating obtained in step (5) at a concentration of 80~130 g / m 2 The amount of product used is coated on the surface of intermediate C obtained in step (4), and after drying and curing, a flame-retardant functional layer is formed to obtain intermediate D; (7) Mix the polydimethylsiloxane prepolymer and the curing agent at a mass ratio of 10: (0.8~1.2) until uniform, then add hydrophobic silica particles and disperse them uniformly to obtain the PDMS / SiO2 composite coating; The amount of hydrophobic silica particles added is 1-10 wt% of the total mass of polydimethylsiloxane prepolymer and curing agent. (8) Apply the PDMS / SiO2 composite coating obtained in step (7) at a concentration of 70~95 g / m 2 The amount of coating used is applied to the surface of intermediate D obtained in step (6), and after curing, a hydrophobic protective layer is formed, resulting in a multifunctional flame-retardant polystyrene foam material with a multi-element synergistic coating.

2. The preparation method according to claim 1, characterized in that: The method for preparing the uncoated polystyrene foam material in step (1) specifically involves pre-expanding and secondary foaming of expandable polystyrene beads to obtain the uncoated polystyrene foam material. The process parameters for the pre-foaming treatment include: pre-foaming pressure of 0.15~0.30 MPa, pre-foaming temperature of 96~108℃, heat preservation time of 1~5 min, and curing time of 4~24 h. The process parameters for the secondary foaming molding include: foaming pressure of 0.15~0.30 MPa, foaming temperature of 115~126℃, and holding time of 5~10 min.

3. The preparation method according to claim 1, characterized in that: The drying process described in steps (2) and (3) is natural drying at a temperature of 20~30℃ or drying at a temperature of 60℃ for 5~15 min.

4. The preparation method according to claim 1, characterized in that: The chemical silver plating process described in step (4) specifically includes: A silver ammonia plating solution was prepared with the following proportions: silver nitrate concentration of 58.9 mmol / L, glucose concentration of 138.8 mmol / L, potassium sodium tartrate concentration of 8.9 mmol / L, ethanol volume fraction of 5%, and the remainder being deionized water. The intermediate B obtained in step (3) was immersed in a silver ammonia plating solution and reacted at a temperature of 20~30 ℃ for 60 min to build a conductive functional layer on the surface of intermediate B. Then it was washed and dried in sequence to obtain intermediate C.

5. The preparation method according to claim 1, characterized in that: The uniform dispersion in step (5) is achieved by first magnetically stirring at 500 rpm for 15 min, and then ultrasonically dispersing at 200 W for 20 min.

6. The preparation method according to claim 1, characterized in that: The drying and curing process described in step (6) is a drying and curing process at a temperature of 20~30℃ for at least 24 hours.

7. The preparation method according to claim 1, characterized in that: The polydimethylsiloxane prepolymer and curing agent mentioned in step (7) are two-component addition-type polydimethylsiloxane.

8. The preparation method according to claim 1, characterized in that: The average particle size of the hydrophobic silica particles in step (7) is 10~100 nm.

9. The preparation method according to claim 1, characterized in that: The curing process described in step (8) is a curing process at a temperature of 60 °C for 4 h.

10. The multifunctional flame-retardant polystyrene foam material with a multi-component synergistic coating prepared by the preparation method of the multifunctional flame-retardant polystyrene foam material with a multi-component synergistic coating as described in claim 1.